Pekan Karya Ilmiah Fakultas Sebagai Upaya Menguatkan Jiwa Kepemimpinan Serta Habituasi Menulis Ilmiah Mahasiswa: Faculty Scientific Work Week as an Effort to Strengthen the Spirit of Leadership and Student Scientific Writing Habituation - Hubi, Zindan Baynal; Fauzi, Aziz; Rizki Adhari, Nursanda; Saepuloh, Dadang; Sudarmaji, Imam (LP2M INSURI Ponorogo, 2025)
The Scientific Work Week of the Faculty of Teacher Training and Education, Syekh Yusuf Islamic University is an activity to strengthen student leadership and the habituation of writing scientific papers among students. Awareness of the culture of writing must always be strengthened, especially among the academic community so that they are not only consumers of information but also producers of thoughts, ideas and concepts that are expressed in written form and are effectively useful in society. This activity lasts for three days with various experts explaining the material according to their respective fields. The steps of this activity are such as leadership strengthening material by experts/organizational activists and material on writing scientific papers by lecturers who have an extraordinary track record of scientific work, then students are divided into several groups with the final assignment given the task of writing an article along with their respective supervisors. Post-activity mentoring for the article assignment is carried out by the post-activity supervisor until the results of the written work made by the group are published in an indexed national journal.